2023
DOI: 10.1167/tvst.12.7.19
|View full text |Cite
|
Sign up to set email alerts
|

Test-Retest Variability and Discriminatory Power of Measurements From Microperimetry and Dark Adaptation Assessment in People With Intermediate Age-Related Macular Degeneration – A MACUSTAR Study Report

Abstract: Purpose The purpose of this study was to assess test-retest variability and discriminatory power of measures from macular integrity assessment (S-MAIA) and AdaptDx. Methods This is a cross-sectional study of 167 people with intermediate age-related macular degeneration (iAMD), no AMD (controls; n = 54), early AMD ( n = 28), and late AMD ( n = 41), recruited across 18 European ophthalmology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
2
1
0
Order By: Relevance
“…Repeatability between the first and the second used device was almost identical suggesting no influence of weariness or learning effect. Similar findings have been reported by other study groups 15 . The shorter test duration of the second examination should be attributed to the used “follow up” function offered by each device instead of a potential learning effect.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Repeatability between the first and the second used device was almost identical suggesting no influence of weariness or learning effect. Similar findings have been reported by other study groups 15 . The shorter test duration of the second examination should be attributed to the used “follow up” function offered by each device instead of a potential learning effect.…”
Section: Discussionsupporting
confidence: 93%
“…Palkovits et al analysed test-retest repeatability for Nidek MP-3 on ten healthy subjects and found similar mean PWS (29.8 ± 0.9), limits of agreement of the Bland-Altman plots (+ 3.54 and − 3.02 dB) and CoR (±3.3 dB) 16 . A similar reproducibility could be attained for test re-test repeatability with the CentreVue MAIA under mesopic conditions while comparing our results to those of Pfau et al who found a CoR of 4.75 dB and similar LoA (+ 4.29 to − 5.08 dB) 24 or Higgins, Bethany E. et al who reported a SD of the within subject differences of 2.62 in a healthy population 15 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…At the summary level, we found that almost all the above modifiable factors were insignificant, as validated in other studies [ 14 , 110 , 111 ]. This is particularly relevant for research groups seeking to validate functional endpoints for AMD (e.g., the ALSTAR2 [ 20 ] and MACUSTAR groups) [ 112 ], whereby the time saved from not performing protracted dark adaptation for mesopic testing, in particular, could be redirected elsewhere. Consistent application of testing protocol at the individual patient level (within populations) is likely still important [ 14 , 25 30 , 32 – 40 , 108 , 109 ].…”
Section: Discussionmentioning
confidence: 99%